1974
DOI: 10.1136/pgmj.50.586.497
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and site of bacteriuria in diabetes mellitus

Abstract: SummaryTwenty-four of 152 female diabetic patients (15.80%) were found to have significant bacteriuria as compared to a prevalence rate of only 4-6% of 152 matched non-diabetic controls. The difference in prevalence rates is statistically significant. However, if the prevalence rates are analysed according to age, bacteriuria was significantly more common only in diabetic females above the age of 50. Localization of site of infection was performed in all diabetic female subjects with bacteriuria. The kidney wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some early studies showed no difference between the frequency of UTI in diabetics compared to controls [9] . But more recent studies documented a two-to-threefold increase of this problem in diabetic women [10] . Kass [2] documented a 16-19% rate of bacteriuria in diabetic women compared to 5-8% in nondiabetic women.…”
Section: Discussionmentioning
confidence: 98%
“…Some early studies showed no difference between the frequency of UTI in diabetics compared to controls [9] . But more recent studies documented a two-to-threefold increase of this problem in diabetic women [10] . Kass [2] documented a 16-19% rate of bacteriuria in diabetic women compared to 5-8% in nondiabetic women.…”
Section: Discussionmentioning
confidence: 98%
“…However, these studies took no account of either the degree of blood sugar control or the severity of the disease. More recent studies found a two-to threefold increase in UTI incidence in diabetic women, particularly in groups with elevated blood glucose levels [12][13][14][15][16]. None of these studies showed a similar increase in risk in men [15].…”
Section: Urinary Tract Infectionsmentioning
confidence: 94%
“…Nevertheless, the reported frequency of UTI in diabetic patients is conflicting [1][2][3][4][5]. Early studies showed no difference between the frequency of UTI in diabetics compared to that in controls [4,6,7], but recent studies have documented a two-to threefold increase of UTI in diabetic women [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%